Treatments of inguinal hernia with sintetic grafts - Maglione, Hugo; Mayol, Ricardo; Torres, Marcos; Veroli, Antonio; Rocca, Guillermo (Cirugía del Uruguay, 1983)
Adventeges of preperitoneal approach by midline subombilicalis incision, for treatment of bilateral inguinalis hernia and hernial recurrency are remarked_ Technical a spects of plastia with sintetic grafts using this approach.are described_ A serie of 24 cases without graft elimination non recurren ·, cy ar presen ted.